2021
DOI: 10.1111/aji.13452
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent changes in placental mRNA expression after delivery due to delayed specimen collection

Abstract: Problem Current scientific guidelines recommend collecting placental specimens within two hours of delivery for gene expression analysis. However, collecting samples in a narrow time window is a challenge in the dynamic and unpredictable clinical setting, so delays in placental specimen collection are possible. The purpose of our analysis was to investigate temporal changes in placental gene expression by longitudinally sampling placentas over a 24 h period. Method of Study Eight placentas from individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Three studies did not report whether the tissue was collected uniformly from the medial or lateral segments of the placenta (Keleher et al, 2021;Mina et al, 2015;Räikkönen et al, 2014) although tissue inflammation has been shown to be more prone in the lateral sections (Burton et al, 2014). Likewise, three of the studies (Keleher et al, 2021;Mina et al, 2015;Muramatsu-Kato et al, 2014) did not report on the sampling time interval, increasing the risk that placental mRNA degradation could have interfered with the results (Burton et al, 2014;Freedman et al, 2021). Furthermore, in the Finish studies (Räikkönen et al, 2014), information on the pregnant women's nutritional habits was not reported, even though licorice, a common exposure in Finland (Räikkönen et al, 2009(Räikkönen et al, , 2010Strandberg et al, 2001), is a potent inhibitor of HSD11β2 and to some extent, an inhibitor of HSD11β1 (Chapman et al, 2013;Räikkönen et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…Three studies did not report whether the tissue was collected uniformly from the medial or lateral segments of the placenta (Keleher et al, 2021;Mina et al, 2015;Räikkönen et al, 2014) although tissue inflammation has been shown to be more prone in the lateral sections (Burton et al, 2014). Likewise, three of the studies (Keleher et al, 2021;Mina et al, 2015;Muramatsu-Kato et al, 2014) did not report on the sampling time interval, increasing the risk that placental mRNA degradation could have interfered with the results (Burton et al, 2014;Freedman et al, 2021). Furthermore, in the Finish studies (Räikkönen et al, 2014), information on the pregnant women's nutritional habits was not reported, even though licorice, a common exposure in Finland (Räikkönen et al, 2009(Räikkönen et al, , 2010Strandberg et al, 2001), is a potent inhibitor of HSD11β2 and to some extent, an inhibitor of HSD11β1 (Chapman et al, 2013;Räikkönen et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%